Mighty crane written by Lori Froeb ; illustrated by Thomas LaPadula - Froeb, Lori; LaPadula, Tom.; Tonka Corporation (New York Reader's Digest Children's Books, 2005)
"It's big. It's tall. It's the TONKA crane! Come onboard and watch as it tears down an old building with a wrecking ball, lifts a crushed car onto a flatbed truck, moves piles of cans at a recycling center and more!"-- P. [4] of cover
Cover title On board pages "For children over 36 months"--P. [4] of cover
Keywords: Cranes, derricks, etc. -- Juvenile Fiction; Toys and movable books